Adoption of Improved Maize Varieties as a Sustainable Agricultural Intensification in Eastern Ethiopia: Implications for Food and Nutrition Security - Mengistu Ketema; Kibebew Kibret; Feyisa Hundessa; Tewodros Bezu (Turkish Journal of Agriculture: Food Science and Technology)
This paper examines factors determining farmers’ adoption decision for improved maize varieties in the maize-common bean intercropping practices in two districts of East Hararghe zone, Eastern Ethiopia. It is based on data collected from 129 farm households using structured questionnaire. Descriptive results revealed that adopters of improved maize varieties had better food and nutrition security status. Furthermore, logit model output indicated that the decision to adopt improved maize varieties is influenced by location (district) dummy, education status of the household head, age of the household head, distance from the main road, and the number of plots owned. Major recommendations include improving the rural road infrastructure, educating and training farmers, organizing experience sharing events among farmers, and raising awareness about the food and nutrition security benefits of sustainable agricultural intensification practices like intercropping improved maize with improved common bean varieties.